SISTEM AKUNTANSI PENCATATAN PERSEDIAAN BAHAN BAKU DENGAN METODE RATA-RATA BERGERAK - Suwandi Suwandi; Freddy Wicaksono; Triana Ramadani (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2019)
CV Sinar Nugraha is a company engaged in the manufacturing industry that produces chili sauce, soy sauce, and syrup. The production process is carried out every day except for syrup products which are only produced during Ramadan. Currently CV. Sinar Nugraha in the activity of recording accounting and inventory reports of raw materials is still manually so that it takes a lot of time and sometimes found errors in recordi The research method used in this study is a descriptive method with a case study, the steps taken are observation and interviews with the manager of the company. The programming language used is PHP Hypertext Prepocessor (PHP), while the database uses MySQL software. This application is made to calculate the cost of raw material inventory using the Moving Average method. And the accounting records use the Perpetual method. The results of this study are a special application program in the form of Raw Material Inventory Accounting Information System for the calculation of the cost of raw material inventory consisting of functions to handle existing procedures, namely procedures for purchasing, spending, and reporting of raw materials. From the results of the implementation and testing it can be concluded that the application that has been made can be applied on the CV. Sinar Nugraha.